Carpine Arthritis - Encephalitis - Σεϊμένης, Α.; Μαστρογιάννη, Μ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The etiology, the symptoms, and the pathologic features of the Caprine Arthritis - Encephalitis are passed in review and the possibilities for control are discussed. The disease as yet is not known to exist In Greece